2011
DOI: 10.1063/1.3598108
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational relaxation of azide ions in liquid-to-supercritical water

Abstract: The dynamics of vibrational energy relaxation (VER) of the aqueous azide anion was studied over a wide temperature (300 K ≤ T ≤ 663 K) and density (0.6 g cm(-3) ≤ ρ ≤ 1.0 g cm(-3)) range thereby covering the liquid and the supercritical phase of the water solvent. Femtosecond mid-infrared spectroscopy on the ν(3) band associated with the asymmetric stretching vibration of the azide anion was used to monitor the relaxation dynamics in a time-resolved fashion. The variation of the vibrational relaxation rate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…Albeit the relatively large number of works on nitrogen chains, not so many other species were considered in a confined environment. In particular, despite the extensive literature investigating the spectroscopic features of the azide ion in crystal or gas phase [34][35][36][37][38][39][40][41][42] as well as solvated [43][44][45][46][47][48][49][50][51][52][53][54][55], N − 3 was never studied in a confined environment. Considering that N − 3 often represents a precursor in the synthesis of energetic molecules, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Albeit the relatively large number of works on nitrogen chains, not so many other species were considered in a confined environment. In particular, despite the extensive literature investigating the spectroscopic features of the azide ion in crystal or gas phase [34][35][36][37][38][39][40][41][42] as well as solvated [43][44][45][46][47][48][49][50][51][52][53][54][55], N − 3 was never studied in a confined environment. Considering that N − 3 often represents a precursor in the synthesis of energetic molecules, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous azide ion solution in this case serves as a model system to study the dynamics and spectral diffusion of solute and solvent molecules because of its absorption in the mid IRregion and dependence of its vibrational frequency on solvent fluctuations. [44][45][46][47][48][49][50] Also, its sophisticated vibrational energy relaxation ranging from room temperature to the supercritical region makes the molecular ion an excellent probe for the solvent dynamics at supercritical condition.…”
Section: Introductionmentioning
confidence: 99%
“…According to their work, the solvent molecule in the vicinity of the ion plays an important role in the spectral diffusion of azide ion at varying condition, however they did not observe any dependence of the vibrational relaxation on the thermal fluctuation and thus found the spectral diffusion of azide asymmetric stretch mode almost unchanged over that wide temperature limits. Followed by the work of Tominaga et al [49], in 2011, Vohringer et al [50] simulated the vibrational relaxation of azide asymmetric stretch mode over a wider range of temperatures (300 K≤T≤663 K) and densities (0.6 g cm −3 ≤T≤1.0 g cm −3 ) using Femtosecond mid-infrared spectroscopy and classical molecular dynamics simulations. First time they were able to give a clear picture of the vibrational spectral diffusion of the azide asymmetric stretch mode as a function of the temperature and density and showed the effect of the local density corrections on the vibrational spectral diffusion of asymmetric stretch mode of the azide ion.…”
Section: Introductionmentioning
confidence: 99%
“…The decay of the frequency-frequency time correlation function of the asymmetric stretch mode of azide ion can be experimentally studied through time dependent infrared spectroscopy and directly related with the fluctuations of the solvation shell. Various experimental [37][38][39][40][41][42][43][44][45] studies have been performed to investigate the dynamical behavior of water molecules in the solvation shells of azide ions such as the frequency fluctuations and dynamics of hydrogen bonds (HBs) in the vicinity of the ions. Generally, it has been reported that the vibrational spectral diffusion of azide asymmetric stretching mode takes place through the hydrogen bond decay channel which points to strong coupling between the azide molecular a) E-mail: amalen@iitk.ac.in ion and surrounding water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…These authors also calculated the absorption line shape and integrated three pulse-echo intensity for the asymmetric stretch mode of azide ion. A subsequent study 45 based on a combination of femtosecond time resolved pump-probe experiment and classical molecular dynamics simulation has shown that solvent molecules generally interact with the terminal nitrogens of the triatomic linear ion and relax the initial asymmetric stretching excitation through such intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%